KEBIJAKAN PEMERINTAH INDONESIA DALAM MENGATASI HAMBATAN FREE TRADE ZONE DI BATAM (STUDI KASUS : HUTAN LINDUNG) - Dewi Fatimah Azzahra; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This study aims to determine how government policies in overcoming the barriers that exist in Batam Batam as a region in realizing a Free Trade Zone (FTZ). The author will focus on one of these obstacles is the problem of protected forest areas in Batam. Free Trade Zone (FTZ) is a region or zone that is getting a policy in the form of facilities or free up some kind of object of trade of some customs rules, including taxes and charges. The method used in this study is a qualitative research method with Study Library (Library Research) technique. This study shows that there are several government policies to overcome the obstacles that exist in Batam Batam as a region in realizing a Free Trade Zone (FTZ). Such as, (1) the Government Regulation (PP) No. 46 of 2007, (2) SK 76/MenLHK-II/2015, and then through (3) And the cooperation between Indonesia and Singapore. Which of these policies have an alternative solution is required.Keywords: Batam, Policy, Free Trade Zone (FTZ), Protected Forest.